A review of antifertility folkloric plants tested in laboratory animals - Damasceno, D. C. [UNESP]; Volpato, G. T. [UNESP]; Lemonica, I. P. [UNESP] (My University, 2002)
The use of natural active principals is widespread among a great proportion of the rural population, or by people who do not have easy access to medical assistance. These active principles are used as food or medicines, and even for purposes of contraception. It becomes necessary to establish a relationship between the folklore habits and current information on the nature of anti-fertility substances, and knowledge of their mechanisms. Anti-fertility agents may exert their actions in a number of areas, (hypothalamus, anterior pituitary, oviduct, uterus, and vagina), inhibiting synthesis and/or liberation of hormones (follicle-stimulating, luteinizing, and steroid hormones), ovulation, ovum transportation, and implantation process. Therefore, a review of literature was carried out, including of several plants used by women as abortifacient and anti-fertility agents to compare their effects with those obtained among laboratory animals.
Keywords: Animals; Anti-fertility; Fertility; Hormones; Medicinal herbs; Plant; Abrus precatorius extract; acacia catechu extract; acalypha indica extract; Adhatoda vasica extract; ailanthus exceisa extract; ambrosia artem isiifolia extract; anona squamosa extract; aristolachia indica extract; artimisia absintum extract; atelela glazioviana extract; azadirachia indica extract; cannabis; carica papaia extract; cassia fistula extract; cinnamomum zeylanicum extract; citrulus colocynthus extract; citrus hystrix extract; coleus barbatus extract; contraceptive agent; Coriandrum sativum extract; croton cajucara extract; cuminum cyminum extract; daucus carota extract; gossypium herbaceum extract; hibiscus rosa sinensis extract; himathanthus sucuuba extract; inula viscosa extract; ipomoea fistulosa extract; unclassified drug; unindexed drug; acacia catechu; acalypha indica; adhatoda vasica; ailanthus exceisa; ambrosia artem isiifolia; anona squamosa; aristolachia indica; artemisia absintum; atelela glazioviana; azadirachia indica; carica papaia; carrot; cassia fistula; Cinnamomum zeylanicum; citrulus colocynthus; citrus hystrix; coleus barbatus; contraception; coriandrum sativum; corpus luteum; croton cajuraca; cumin; dimorphandra mollis; drug identification; endometrium; fertilization; Gossypium herbaceum; health care access; hibiscus rosa sinensis; himathanthus sucuuba; hormone release; hypophysis; hypothalamus; inula viscosa; ipomea fistulosa; medicinal plant; nidation; nonhuman; oocyte transport; oviduct; ovulation; review; rural population; steroidogenesis; traditional medicine; uterus; vagina; Abrus precatorius; Acacia catechu; Acalypha indica; Ailanthus; Ambrosia; Animalia; Areca catechu; Artemisia; Cannabis; Carica; Cassia fistula; Citrulus; Citrus hystrix; Coleus barbatus; Coriandrum sativum; Croton; Croton cajucara